2021
DOI: 10.3389/fpubh.2021.818439
|View full text |Cite
|
Sign up to set email alerts
|

Development and Internal Validation of a Nomogram to Predict Mortality During the ICU Stay of Thoracic Fracture Patients Without Neurological Compromise: An Analysis of the MIMIC-III Clinical Database

Abstract: Background: This study aimed to develop and validate a nomogram for predicting mortality in patients with thoracic fractures without neurological compromise and hospitalized in the intensive care unit.Methods: A total of 298 patients from the Medical Information Mart for Intensive Care III (MIMIC-III) database were included in the study, and 35 clinical indicators were collected within 24 h of patient admission. Risk factors were identified using the least absolute shrinkage and selection operator (LASSO) regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 70 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The nomogram is a visualization tool used to generate the probability of clinical outcome (Park, 2018). Studies have demonstrated that nomogram enable accurate compared to traditional scoring systems (Wang et al, 2021). It is now widely used for risk Frontiers in Pharmacology frontiersin.org prediction of many diseases (Li et al, 2021;Tan et al, 2022;Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram is a visualization tool used to generate the probability of clinical outcome (Park, 2018). Studies have demonstrated that nomogram enable accurate compared to traditional scoring systems (Wang et al, 2021). It is now widely used for risk Frontiers in Pharmacology frontiersin.org prediction of many diseases (Li et al, 2021;Tan et al, 2022;Wang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The nomogram model of the hub genes was constructed using the R RMS package (version 6.0-1) ( Zhao and Li, 2023 ), and a calibration curve was drawn using the calibration function and boot method. The accuracy of the nomogram model for predicting osteoporosis was determined using the slope of the curve and Hosmer-Lemeshow goodness-of-fit test (HL test), where the insignificant difference ( p > 0.05) between predicted and actual observed results in HL test indicates that the prediction model has good calibration ability ( Wang et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Multiple interpolation was used to estimate and fill in the missing data. Variables with >20% of missing data were excluded 15 . Lactate was converted to a dummy variable in the model to avoid possible bias caused by the filled missing values.…”
Section: Methodsmentioning
confidence: 99%